An analysis of the appropriateness of the four funds approach for the taxation of life insurers in South Africa including a qualitative comparison to the recently enacted approach adopted in New Zealand and recommendations for improvement to the approach - Donaldson, Peter Allen (Department of Commercial Law, 2015)
Section 29A of the Income Tax Act No. 58 of 1962 contains a special set of rules for the taxation of life insurers. These rules were originally enacted in 1993 and are commonly referred to as the four funds approach. The rules have remained largely unchanged since their original enactment despite ongoing changes in the life insurance industry in particular with regards to new product offerings.